«New tourists» in Faro's historic centre - Ferreira, Ana (2006)
Paradigmatic changes in the twentieth century gave rise to processes of progressive cultural integration which encouraged the formation of a «new middle class» looking for cultural satisfaction. For mature sea and sun tourist destinations, the cultural practices of these «new tourists» may help to regenerate historic town centres, as this research carried out in Faro seems to show.